Diagnostic Methodologies of Laser-Initiated 11B(p,α)2α Fusion Reactions - Consoli, Fabrizio; De Angelis, Riccardo; Andreoli, Pierluigi; Bonasera, Aldo; Cipriani, Mattia; Cristofari, Giuseppe; Di Giorgio, Giorgio; Giulietti, Danilo; Salvadori, Martina (Frontiers in Physics, 2020)
The detection of the ionic products of low-rate fusion reactions, and in particular of the 11B(p,alpha)2alpha, is one of the recognized main problems in experiments where these reactions are initiated by tailored interaction of intense and high-energy lasers with matter. A thorough description of this important issue, with the critical comparison of the diagnostic opportunities, is indeed so far missing. In this work, we describe the common diagnostic methodologies used for the detection of the alpha particles generated by the 11B(p,alpha)2alpha reaction and, for each, we outline advantages and limitations, with considerations that can be also applied to other low-rate fusion reactions. We show here that, in general, the univocal characterization of the alpha products coming from this reaction can be achieved by the simultaneous use of several diagnostics tools placed in close proximity.